The role of IL17 and IL17RA polymorphisms in lethal pandemic acute viral pneumonia (Influenza A virus H1N1 subtype) - Vanessa Yumie Salomão Watanabe Liberalesso; Marina Luise Viola Azevedo; Mineia Alessandra Scaranello Malaquias; Caroline Busatta Vaz de Paula; Seigo Nagashima; Daiane Gavlik de Souza; Plínio Cézar Neto; Kauana Oliveira Gouveia; Larissa Cristina Biscaro; Ana Luisa Garcia Giamberardino; Gabrielle Tasso Gonçalves; Thais Teles Soares Kondo; et al. (BMC, 2023)
Abstract Background The cytokines play an essential role in acute inflammatory processes, and the IL-17 may be responsible for ambiguous aspects, and the correlation with genetic polymorphisms could improve the search for this critical biomarker. Thus, this study aimed to evaluate the IL-17A and IL-17RA tissue expression and the polymorphisms that codified these proteins in a population that died of pandemic Influenza A virus H1N1 subtype compared to a non-pandemic Influenza virus population. Methods Necropsy lung samples immunohistochemistry was performed to assess the presence of IL-17A and IL-17RA in the pulmonary tissue. Eight single nucleotide polymorphisms were genotyped using TaqMan® technology. Results The Influenza A H1N1 pandemic group had higher tissue expression of IL-17A, higher neutrophil recruitment and shorter survival time between admission and death. Three single nucleotide polymorphisms conferred risk for pandemic influenza A H1N1, the AA genotype of rs3819025 G/A, the CC genotype of rs2241044 A/C, and the TT genotype of rs 2,241,043 C/T. Conclusions One IL17A polymorphism (rs381905) and two IL17RA polymorphisms (rs2241044 and rs2241043) represented biomarkers of worse prognosis in the population infected with pandemic influenza A H1N1. The greater tissue expression of IL-17A shows a Th17 polarization and highlights the aggressiveness of the pandemic influenza virus with its duality in the protection and pathogenesis of the pulmonary infectious process.